Case of Nickel Ore Export Trade Dispute Between Indonesia and the European Union and Its Resolution from an International Legal Perspective - Putri, Aprilia Puspitasari (International Law Discourse in Southeast Asia, 2024)
In this article, we will discuss the case of the nickel ore export trade dispute between Indonesia and the European Union from an international legal perspective. The European Union has issued a policy restricting imports of nickel ore from Indonesia which is considered to violate international trade agreements. Indonesia responded and filed a lawsuit with the World Trade Organization (WTO) and asked for dispute resolution through the WTO dispute resolution mechanism. This article will discuss how to resolve disputes between Indonesia and the European Union. This case is very complex regarding nickel ore because Indonesia is the largest supplier of this natural resource.